Effect of oral glucose administration on pain in neonates undergoing peripheral blood collection - Effa Triani; Munar Lubis; Chairoel Yoel (Paediatrica Indonesiana, 2007)
Background Peripheral blood sampling with heel sticks in neonatescould represent minor invasive procedure which generates pain.The oral glucose administration can reduce the pain in neonatesduring this procedure.Objective To compare the pain sense after oral glucoseadministration or placebo during peripheral blood sampling withheel sticks in neonates.Methods A double blind randomized clinical trial study wasconducted from January to March 2004 in three teaching hospitalsin Medan. The population of this study was divided into twogroups (glucose and placebo) and each group consisted of 32neonates. The intervention group got 1 ml of 40% glucose andthe placebo group got 1 ml of sterile water. Blood sample wastaken with sterile hemolet with heel sticks from healthy atermneonates. The pain was measured using NIPS score and measuredin first 30 seconds after heel sticking. The heart and respiratoryrate measurement was done before and during the interventionand we also counted crying time. Data were analyzed with studentt–test.Results The significant mean difference of NIPS score in glucosegroup was 2.22 (SD 0.83) vs 4.72 (SD 0.96) in placebo group(P<0.0001). There was significant mean difference of crying time,i.e. 0.16 (SD 0.37) in glucose group vs 2.05 (SD 0.77) in placebogroup (P<0.0001). There was significant differences of heart ratebefore and during heel sticking in both groups.Conclusion There were some differences of pain sense in neonateswho received 40% glucose compared to those who received sterilewater during peripheral blood sampling.